Measurement precision for Oswestry Back Pain Disability Questionnaire versus a web-based computer adaptive testing for measuring back pain. - Bongsam Choi (Journal of Back & Musculoskeletal Rehabilitation, 2015)
BACKGROUND AND OBJECTIVES: Relative precision is to denote the ratio of the error variance of two sample designs. The aim of the present study was to compare measurement precisions of the Oswestry Back Pain Disability Questionnaire and a computer adaptive testing (CAT) method for measuring disability resulting from back pain. MATERIAL AND METHOD: A cross-sectional study was carried out with two independent convenient samples from two out-patient rehabilitation clinics for back pain (N = 42) and non-back pain groups (N = 42). Participants were asked to fill out the ODQ and CAT of International Classification of Functioning, Disability and Health – Activity Measure (ICF-AM). A series of Rasch analyses were performed to calculate person ability measures. RESULTS: The CAT measures had greater precision in discriminating the groups than did the ODQ measure in comparisons of the relative precision. CONCLUSIONS: The CAT measure appears to be more effective than the ODQ measure in terms of measurement precision. By administering test items calibrated in a way, CAT measures using item response theory may promise a means with measurement precision as well as efficiency.